The Impact of the Rwanda Genocide on the Development of International Humanitarian Law - Lala Anggraita Permata Aji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Rwandan genocide in 1994 was one of the worst humanitarian tragedies in modern history, killing an estimated 800,000 people in less than 100 days. This event not only left deep wounds for the Rwandan people, but also had a significant impact on the development of international humanitarian law. This abstract examines how the Rwandan genocide prompted a revision and strengthening of international legal principles, including enforcement mechanisms, refugee protection, and trials for international crimes. Through an analysis of UN Resolutions, the establishment of the International Criminal Tribunal for Rwanda (ICTR), and developments in the Geneva Conventions, the article shows that the Rwandan genocide has influenced the way the international community has responded to future armed conflicts and human rights violations.